How Australia compares - Tiffen, Rodney (Cambridge University Press, 2004)
Australians find it difficult to compare themselves with the world because they exist as a developed English-speaking nation so far from the metropolitan centers of Europe and the U.S. Assessing the nation in relation to its broader group of peers, this book compares and contrasts Australia over 17 core aspects of economic, political and social life with 18 leading first-world countries. Rod Tiffen and Ross Gittins interpret the data and communicate its implications in this comprehensive reference work